TNFR2 blockade alone or in combination with PD‐1 blockade shows therapeutic efficacy in murine cancer models. Issue 6 (24th May 2020) - Case, Katherine; Tran, Lisa; Yang, Michael; Zheng, Hui; Kuhtreiber, Willem M.; Faustman, Denise L.
Abstract: Immune checkpoint inhibitors are profoundly transforming cancer therapy, but response rates vary widely. The efficacy of checkpoint inhibitors, such as anti‐programmed death receptor‐1 (anti‐PD‐1), might be increased by combination therapies. TNFR2 has emerged as a new target due to its massive expression on highly immunosuppressive regulatory T cells (Tregs) in the microenvironment and on certain tumor cells. In murine colon cancer models CT26 and MC38, we evaluated the efficacy of a new anti‐TNFR2 antibody alone or in combination with anti‐PD‐1 therapy. Tumor‐bearing mice were treated with placebo, anti‐PD‐1 alone, anti‐TNFR2 alone, or combination anti‐PD‐1 and anti‐TNFR2. We found that combination therapy had the greatest efficacy by complete tumor regression and elimination (cure) in 65–70% of animals. The next most effective therapy was anti‐TNFR2 alone (20–50% cured), whereas the least effective was anti‐PD‐1 alone (10–25% cured). The mode of action, according to in vivo and in vitro methods including FACS analysis, was by killing immunosuppressive Tregs in the tumor microenvironment and increasing the ratio of CD8+ T effectors (Teffs) to Tregs. We also found that sequence of antibody delivery altered outcome. The two most effective sequences were simultaneous delivery (70% cured) followed by anti‐TNFR2 preceding anti‐PD‐1 (40% cured), and the least effective was by anti‐PD‐1 preceding anti‐TNFR2 (10% cured). We conclude that anti‐PD‐1 is best enhanced by simultaneous administration with anti‐TNFR2, and anti‐TNFR2 alone may be potentially useful strategy for those do not respond to, or cannot tolerate, anti‐PD‐1 or other checkpoint inhibitors. Abstract : Immune checkpoint failures have tumor infiltrates with TNFR2+ Tregs; anti‐TNFR2 with anti‐PD1 antibody therapy in mice now leads to frequent cures, eliminating Treg driven failures.